RA V14 N3, Message from the Editor in Chief (September – December, 2024) - Castro Borges, Pedro (Revista ALCONPAT, 2024)
LATIN AMERICAN JOURNAL OF QUALITY CONTROL, PATHOLOGY AND CONSTRUCTION RECOVERY http://www.revistaalconpat.org It is a source of satisfaction and joy for the ALCONPAT Journal team to see the third issue of our fourteenth year published. The objective of the Revista ALCONPAT (RA) is the publication of citable production (basic or applied research, and reviews), documentary research and case studies, related to the themes of our association, i.e. quality control, pathology and recovery of constructions. In this V14 N3 of the Alconpat Journal, the Editorial Committee is pleased to have as Guest Editors Doctors Roberto Christ (President of Alconpat Brazil) and Enio Pazini (President of Alconpat International), who have done an excellent job in the selection, evaluation and approval of the works that appear in this issue. These works responded to the call for best works sent to the Brazilian Congress of Construction Pathology (CBPat 2024) under the theme of "Strategies, methods, materials and technology to confer durability and sustainability to concrete infrastructure". This issue V14 N3, starts with a paper from Brazil, Colombia and Russia, where Roberto Christ and colleagues evaluate the mechanical behaviour of GRP in solid concrete slabs. The use of glass fibre reinforced polymer (GRP) reinforcing bars in building design has been an alternative technique to provide more durable structures. However, it is necessary to evaluate the behaviour of GRP reinforced slabs under bending and compare the serviceability state (SS) and ultimate serviceability state (USS) of the loaded element. Thus, reinforced concrete slabs of different thicknesses were constructed with steel and GRP reinforcing bars. The results show that the applied load for the maximum span deflection of the GRP slab under SS was 50% lower than that for the steel reinforced plate. The maximum span deflection of the GRP slab under USS was also 282% higher than that of the steel reinforcing bar reinforcement. In the second work, from Brazil, Palloma Borges Soares and colleagues present the computational modeling of reinforced concrete beams, reinforced in shear with carbon fiber reinforced polymers (CFRP), using the finite element method (FEM) and using the customized ANSYS software, version 19.2. It is important to highlight that to model the concrete-reinforcement interface, contact elements and bilinear cohesive zone models available from ANSYS were used. These models were used in order to identify the premature failure modes caused by the detachment of the reinforcement, which causes a poor use of the strength properties of CFRP. The structural elements used in this analysis were twelve reinforced concrete beams with and without shear reinforcement with CFRP, which were tested experimentally by Khalifa (1999). From the analysis of the results, it was found that the developed numerical models were able to predict with good accuracy the behavior of the simulated beams, both in terms of load-displacement and the load and failure mode of the beams. The third work in this issue is from Brazil, where Igor Rossi Remenche and colleagues investigate how incipient anodes can be detected and monitored in localized repair areas with mortars containing rice husk silica addition. Three repair conditions were tested on prismatic specimens: without repair, with repair without rice husk silica addition and with rice husk silica addition in the mortar. Corrosion potential and electrical resistivity tests were performed. It was concluded that the addition of rice husk silica to the mortar made the corrosion potential more electronegative due to the greater difference in electrical resistivity relative to the substrate, contributing to the formation of the incipient anode. The fourth article, by Joici Rizzo and colleagues, comes from Brazil. They conducted a study where the mechanical behavior of reinforced concrete structures with one and two layers of the Brazilian glass fabric “AR-360” was verified, through direct tensile tests. The analysis of the mechanical behavior of the structures was carried out through stress versus strain graphs, evaluating the transition points of the formed stages, rupture mode, stress and strain at rupture, as well as an analysis comparing experimental results with analysis. Regarding the results, a structural incapacity of the pieces reinforced with a layer of glass fabric was found. In the samples in which the reinforcement with two layers of the aforementioned material was evaluated, the three stages present in the stress-strain curves were correctly identified, as predicted by the literature for the evaluated structures. The fifth article from Brazil is by Weiglas Soriano Ribeiro and colleagues. In this paper, they show us how pathological manifestations in buildings, arising during the construction process or throughout their useful life, can impair the performance of the structure. Traditional approaches to detect these anomalies require time, effort and visual skill on the part of experts. However, advances in computer vision have resulted in the development of tools based on machine learning, capable of detecting pathological manifestations in real time, accurately and efficiently. This study highlights the successful application of deep neural networks in the automation of crack detection and localization in images. Using images collected from the Internet, the YOLO v8 network was trained, achieving solid metrics in training, validation and testing, despite performance limitations in Google Collab. Validation with images not used in training achieved an accuracy of 80%. The relevance of this tool in automated crack detection is evident, generating large-scale information to support decision making. Although the current model is specific to cracks, its applicability can be extended to other pathological manifestations, expanding its potential in the automated identification of problems in buildings. The sixth paper is by Elayne Valério Carvalho and colleagues from Brazil. This paper documents the pathological manifestations of the Casarão dos Fabricantes, one of the oldest buildings in Fortaleza, which was destroyed in 2020 by a large fire. Despite its historical relevance, there are no records of the conditions of this building before or after the fire. The internal walls and two facades were the only construction elements that were not destroyed by the fire. For this purpose, visual assessment and infrared thermography were used. The survey of the pathological manifestations indicated that the evaluated structures presented different degradation processes, providing a systematic view of the extent of the damage to the building. Mapping these damages provided an integrated approach, from a scientific point of view, helping in the restoration process. The seventh article from Brazil is by Marcelo da Costa Bordinhão and colleagues, who assess the contribution of the Unmanned Aerial Vehicle (UAV) in the identification and quantification of pathological manifestations on the facades of the DTIC building of the Federal University of Pampa (UNIPAMPA) Alegrete/RS campus, before and after six months of its maintenance. Images and inspection sheets were used to prepare the Damage Maps and the Gradation Method for quantification. The comparison of the maps, before and after the maintenance, revealed that the intervention (painting) was ineffective, temporarily hiding the anomalies without correcting them. The use of Unmanned Aerial Vehicles proved to be a good tool for inspection, providing time savings, effective diagnosis and safety to the operator, eliminating the need to work at height. The article that closes the issue is by Cristhiana Albert and colleagues from Switzerland and the United States, who present research in which they mention that reducing greenhouse gas emissions in concrete production is crucial to achieving sustainability goals. One of the main solutions is the use of environmentally friendly cements with lower clinker content, as is the case of cements containing supplementary cementitious materials. However, concrete produced with some of these cements may be susceptible to a faster carbonation process, raising questions related to reinforcement durability and corrosion. Although traditional approaches focus on preventing concrete carbonation and corrosion initiation, evidence shows that steel corrosion rates in carbonated concrete do not necessarily compromise its durability. In this context, the fundamental level understanding of corrosion kinetics needs to be improved, considering the role of concrete pore solution, pore structure and moisture content, aspects discussed in this paper. Open questions and promising approaches to clarify them are also discussed. Based on this knowledge, the corrosion propagation phase can be appropriately included in the service life design of reinforced concrete structures, reconciling the objectives of sustainable and durable structures. We are confident that the articles in this issue will be an important reference for those readers involved in issues of evaluation and characterization of materials, elements and structures. We thank the authors participating in this issue for their willingness and effort to submit quality articles and meet the established deadlines. Fourteen years after starting operations, our performance as Alconpat Journal was finally rewarded with our inclusion in one of the two best indexes for journals such as Elsevier’s Scopus. We already have a modest impact factor (0.3), which I am sure will increase thanks to you, our readers, and the quality of our articles. Our membership in Scopus has its historic beginning on December 29, 2022, the date on which we received approval from Elsevier. We hope during 2025, when we will celebrate 15 years of being on the air, to apply to Journal Citation Reports, which is the index with the highest international coverage and quality. These are reasons for celebration for our community that has made a scientific investment in our journal waiting for moments like this. Congratulations to all. By the Editorial Board Pedro Castro Borges Editor in Chief